Effects of codeine on esophageal peristalsis in humans using high resolution manometry. Issue 12 (10th August 2021) - Chen, Chien‐Lin; Wong, Ming‐Wun; Hung, Jui‐Sheng; Liang, Shu‐Wei; Liu, Tso‐Tsai; Yi, Chih‐Hsun; Lin, Lin; Orr, William C.; Lei, Wei‐Yi
Abstract: Background and Aim: Opioid receptors agonists have been demonstrated to impair lower esophageal sphincter (LES) relaxation and induce spastic esophageal dysmotility, but little was known for their impact on distension‐induced secondary peristalsis. The aim of the study was to investigate the hypothesis whether acute administration of codeine can influence physiological characteristics of primary and secondary peristalsis in healthy adults. Methods: Eighteen healthy volunteers (13 men, mean age 27.5 years, aged 20–43 years) underwent high resolution manometry (HRM) with a catheter containing an injection port in mid‐esophagus. Secondary peristalsis was performed with 10 and 20 mL rapid air injections. Two different sessions including acute administration of codeine (60 mg) or the placebo were randomly performed. Results: Codeine significantly increased 4‐s integrated relaxation pressure (IRP‐4s) ( P  = 0.003) and shortened distal latency (DL) ( P  = 0.003) of primary peristalsis. The IRP‐4s of secondary peristalsis was also significantly higher after codeine than the placebo during air injections with 10 mL ( P  = 0.048) and 20 mL ( P  = 0.047). Codeine significantly increased the frequency of secondary peristalsis during air injections with 10 mL than the placebo ( P  = 0.007), but not for air injection with 20 mL ( P  = 0.305). Conclusions: In addition to impair LES relaxation and reduce distal latency of primary peristalsis, codeine impairs LES relaxation of secondary peristalsis and increases secondary peristaltic frequency. Our study supports the notion in human esophagus that the impact of opioids on peristaltic physiology appears to be present in both primary and secondary peristalsis.